Cibo, educazione e ricerca: costruire un futuro sostenibile (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Educating young people to active citizenship is becoming a priority to make better informed choices and promote sustainable behaviours. Food system information provides a good example, because the way we eat is linked to our health and the one of Planet. In Italian schools, the number of available food education modules is growing. However, most of them stress purely nutritional aspects and focus on the food system is relatively sparse. This paper presents an innovative way of teaching and develop global citizenship competences through food with a project called “We, Food, Our Planet”.
Keywords: Food sustainability; education; teachers; active citizenship; Novel Food